Comparative molecular analysis of isogenic clones of Trypanosoma (Nanommonas) congolense that differ in their response to isometamidium chloride - Majiwa, Phelix A.O.; Maina, M.; Peregrine, A.S.; Kasumba, I. (Monduzzi Editore S.p.A., 1998)
Two clones of Trypanosoma (Nannomonas) congolense were derived one from the other by growth in mice and administration of increasing sub-curative doses of isometamidium chloride. One of the clones thus became approximately 10x more tolerant to the trypanocide than the other mRNA from the two clones was used in the construction of cDNA libraries. As an initial step in the search for differences in transcription patterns in trypanosomes that differ in their response to the trypanocide, the cDNAs from the isogenic clones of T. congolense were compared by differential hybridization and differential display. The polymorphic transcripts identified were cloned, sequenced and the sequences compared with those in GenBank. Approximately 30 percent were significantly homologous to known genes. Analysis of these should provide clues regarding molecular genetic basis of T. congolense resistance to isometamidium chloride.